The Influence of Work Discipline and Work Motivation on Performance High School Teacher N 1 Mulak Ulu - Hernisa Juita; Hestin Hestin; Rudi Eduar (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of work discipline and work motivation on teacher performance at SMA N 1 Mulak Ulu. This study employed a quantitative approach with a causal associative method. The data sources used were primary data sources and secondary data, with a questionnaire as the field research data collection method. The respondents in this study were 46 teachers at SMA N 1 Mulak Ulu. The requirements tests used were validity and reliability tests. The analytical method used was multiple regression analysis. The hypothesis tests used were the T-test and F-test. The results showed that work discipline had a positive and significant effect on teacher performance, and work motivation had a positive and significant effect on teacher performance. Simultaneous hypothesis testing shows that work discipline and work motivation together have a positive effect on teacher performance with a contribution of 88.8%, while the remaining 11.2% is influenced by other variables not examined.